Contrast-enhanced ultrasound (CEUS) reliably rules out neoplasm in developmental renal pseudotumor. (June 2021) - Spiesecke, Paul; Fischer, Thomas; Maxeiner, Andreas; Hamm, Bernd; Lerchbaumer, Markus H
Background: Renal pseudotumors appear as benign cortical hypertrophies and are typically assessed by contrast-enhanced computed tomography or magnetic resonance imaging to rule out malignancy. Purpose: To investigate whether contrast-enhanced ultrasound (CEUS) can rule out renal neoplasm and thus potentially reduce cross-sectional imaging and further follow-up in these patients. Material and Methods: Thirty-two patients with presumption of developmental renal pseudotumor on CEUS between June 2011 and July 2019 were retrospectively analyzed. All patients were examined with a standardized renal US protocol including B-mode, color-coded duplex sonography (CCDS), and CEUS by an experienced radiologist (EFSUMB level 3). Images were retrospectively interpreted in consensus by two highly experienced radiologists. Histopathological reports, cross-sectional imaging findings, and clinical course (treatment response, long-term imaging follow-up) were defined as standard of reference. Results: CEUS correctly identified 8/9 neoplastic lesions and missed one oncocytoma within the 32 included patients. Irregular vessel structure (88.9% vs. 13.0%, P  = 0.007) and hyperenhancement (66.6% vs. 17.4%, P  = 0.031) on CEUS were more common in neoplasm compared to developmental pseudotumors reaching statistical significance. Compared with the standard of reference, CEUS had 89% sensitivity (95% confidence interval [CI] 57–98), 96% specificity (95% CI 80–99), a positive predictive value of 89% (95% CI 57–98), and a negative predictive value of 96% (95% CI 79–99) for ruling out renal malignancy in developmental pseudotumors. Conclusion: CEUS is a safe and fast method to rule out neoplasm in the diagnostic work-up of renal pseudotumors. In conjunction with B-mode and CCDS, CEUS has the potential to reduce further (invasive) diagnostic procedures.